Perceptions of persons linked to long-term care services. A scoping review (Horizontes de Enfermería, 2018)
This scoping review examines perceptions about long-term care services from the perspective of different actors. The current concern about this issue is based on the growing demographic aging of countries around the world because this population increase implies a greater demand for care services, especially in older people. Despite the concern that exists about long-term care services, there is little evidence to recognize how people who are in some way linked to this type of service, receive the benefits that are granted according to the offer of services that the countries present. Consequently, the justification for conducting a scoping review is based on detecting knowledge gaps around the problem in order to continue the lines of research than close this lack of knowledge. The review question that guided this study was what is known in the published literature about the perceptions of older people, caregivers, workers, voluntary people, decision-makers and researchers about long-term care services? This scoping review was divided into six sections suggesting that there is limited knowledge of the range of services and barriers involved in access, as well as  is the most appropriate according to their situation, and finally study the underrepresented actors in the provision of care, as is the case of volunteers. In this sense, it is necessary to carry out more studies that allow establishing different socio-cultural perspectives of the people involved in the care, independently if they belong to countries with care policies already established or not.
Keywords: perceptions; long-term care services; scoping review